Overview of patient responses to pain stimuli based on glasgow coma scale (GCS) scores - Abdul Malik; Emil Huriani; Fitri Mailani (Science Midwifery, 2025)
Decreased consciousness is a clinical condition that requires rapid and accurate assessment. One method used is the application of nail bed pressure pain stimulation to elicit a response from the patient. This study aims to determine the consistency of responses from patients with decreased consciousness when given pain stimulation based on the Glasgow Coma Scale (GCS) score in the emergency department of Dr. M. Djamil Hospital in Padang. This was a quantitative descriptive study with 70 respondents selected using purposive sampling. Consciousness levels were measured twice. Data were collected in July 2025 using the GCS assessment format, then analyzed descriptively and cross-tabulated using frequency distribution, percentages, means, standard deviations, and correlations. The nail bed pressure technique produced an average GCS score of 6.01 ± 0.625 on the first assessment and 6.04 ± 0.711 on the second assessment. Most scores were in the range of 6–7. The nail bed pressure technique provided an inconsistent picture of changes in GCS responses in patients with decreased consciousness.